APPLICATION OF POTENTIAL MODEL IN THE ANALYSIS OF REGIONAL DIVERSITY OF AGRICULTURE IN POLAND - Tłuczak, Agnieszka (Acta Universitatis Lodziensis. Folia Oeconomica, 2015)
Polish agriculture and rural areas are characterized by regional differentiation that is dependent on natural conditions, but increasingly also non-natural. The differences in the spatial level of agricultural development have an impact on manufacturing potential, efficiency and ability to generate income. In the analyses of regional development the potential models are used. In their case the correlation analysis is carried, which allows to explore the relationship between potential and other socio-economic phenomena. In the analysis of the region the potential is a measure of the impact of the regions in the given system. The aim of this study is to examine the regional differentiation of Polish agriculture, to extract the core and peripheral regions on the basis of the potential model. The research was conducted at the level of provinces.